Transormasi Pengembangan HRD melalui Pendekatan Sistem Keputusan Berbasis Data untuk Meningkatkan Kinerja Organisasi - Alya Zia Annisa; Tengku Maryam Arief Delikhan; Nabila Veronica; Abdurrozzaq Hasibuan (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
The transformation of Human Resource Development (HRD) through a data-driven decision-making system has become a strategic necessity for organizations aiming to improve performance and competitiveness. This study employs a qualitative descriptive approach by reviewing several relevant journals that discuss the integration of data analytics into HRD functions. The findings indicate that data-driven decision systems enable organizations to accurately identify training needs, predict employee performance, and design development programs that align with evolving organizational demands. Furthermore, the use of data reduces subjective bias in evaluation processes and enhances the objectivity of performance assessments. This transformation also strengthens the strategic role of HRD by providing timely and evidence-based recommendations that support organizational goals. However, successful implementation requires technological readiness, digital competencies among HR personnel, and an organizational culture that encourages data utilization. Overall, the literature review shows that adopting data-driven decision approaches significantly contributes to improving HRD effectiveness and organizational performance.